Behaviour of Slabs Under Impact Loading: A Review - Daud, Raid A.; Daud, Sultan; Al-Allaf, Mustafa H.; Alrshoudi, Fahad (Al-Nahrain Journal for Engineering Sciences, 2025)
The behaviour of slabs under impact loading differs significantly from that observed under short-term or long-term static loading conditions. Such dynamic loading scenarios typically arise from vehicular collisions, explosive events, or other forms of sudden impact. This paper aims to synthesise and critically evaluate the extant literature concerning the response of slabs subjected to impact loading. The investigation encompasses an analysis of the salient factors influencing slab behaviour, elucidation of failure mechanisms, examination of methodologies for simulating impact loading, and a critical appraisal of pertinent design code recommendations. Through this comprehensive review, it has been ascertained that reinforcement configuration plays a pivotal role in augmenting the resistance of slabs to impact loading. Furthermore, the predominant mode of failure observed in such scenarios is punching shear. This finding underscores the necessity for meticulous consideration of shear capacity in the design of impact-resistant slab structures.